Climate Adaptation Policies and Infant Health: Evidence from a Water Policy in Brazil - Daniel Da Mata; Lucas Emanuel; Vitor Pereira; Breno Sampaio (Institute of Labor Economics (IZA), 2021)
This paper studies how in utero exposure to a large-scale climate adaptation program affects birth outcomes. The program built around one million cisterns in Brazil's poorest and driest region to promote small-scale decentralized rainfall harvesting. Access to cisterns during early pregnancy increased birth weight, particularly for more educated women. Data suggest that more educated women complied more with the program's water disinfection training, highlighting that even simple, low-cost technologies require final users' compliance ("the last mile") to be effective. In the context of growing water scarcity, adaptation policies can foster neonatal health and thus have positive long-run implications.
Keywords: Q54; Q58; Q25; I15; 330; birth outcomes; adaptation; climate; cisterns; water